The Role of Risk Based Internal Audit and Risk Management in the Prevention and Detection of Fraud in Auction Companies (Study Case at PT JBA Indonesia) - Zahra, Silmy Auliya (Indonesian Journal of Economics, Social, and Humanities, 2025)
The benchmarking report on Anti-Fraud Technology published by ACFE (2024) revealed that companies in the field of transportation are at significant risk of fraud, especially with the emergence of more sophisticated technology used by fraud perpetrators. Therefore, it can be determined that the purpose of this study is to determine and understand the role of risk-based audit internal and risk management in Detection and prevention of fraud in auction companies specifically at PT JBA Indonesia which is the subject of this study. This research was conducted using a qualitative method, with primary data collected in the form of interviews and secondary data collected in the form of journals, books that are relevant to the research topic, and previous research. The results of this study are that audit internal contributes through evaluating and strengthening internal controls, the adoption of a risk-based approach, increasing Anti-Fraud awareness, and utilizing technology such as WBS to receive reports of indications of fraud. On the other hand, risk management focuses on preparing and updating risk registers, collaborating with the Anti-Fraud team to develop recommendations and mitigation, collaborating with the audit internal team for preventive measures, and conducting in-depth analysis of fraud incidents to identify root causes. Based on the research that has been conducted, there are recommendations for future research such as expand the research subject, combine research methods into a mix method, develop a new fraud analysis theory, which is 5W + 5H, and use additional tools such as NVIVO, MAXQDA, SPSS, and others.